Anti-ultraviolet coating composition resistant to seawater corrosion
By using materials such as modified basalt scales and nano-aluminum powder in anticorrosion coatings, combined with ultrasonic treatment technology, the problem of fast corrosion rate in seawater environments is solved, and higher corrosion resistance and UV resistance are achieved, extending the coating life and suitable for outdoor applications.
Patent Information
- Application Number
- CN202411178255.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-27
AI Technical Summary
Existing anticorrosion coatings corrode rapidly in seawater environments, especially in tidal and splashing areas, resulting in a shorter coating life and limited effectiveness of conventional light stabilizers against ultraviolet rays.
A seawater corrosion-resistant UV coating composition is adopted, including 50 to 80 parts of aqueous epoxy resin, 30 to 50 parts of filler, 10 to 40 parts of epoxy resin amino curing agent, 0.2 to 0.8 parts of dispersant, 0.5 to 2 parts of thickener and 2 to 8 parts of nano-aluminum powder, and the basalt scales are modified by ultrasonic treatment to improve the compatibility and UV resistance of the coating.
It significantly improves the corrosion resistance and UV resistance of the paint, extends the life of the coating, and expands its application range, and is suitable for outdoor outdoor places.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion coatings, and in particular relates to an anti-ultraviolet coating composition resistant to seawater corrosion. Background Art
[0002] Steel in tidal zones and splash zones corrodes quickly under the action of splashing seawater. For example, for cross-sea bridges, the wind barriers on both sides are made of metal. Under the action of seawater, these wind barriers corrode quickly. At the same time, after the on-site construction workers have sprayed anti-corrosion paints many times, such as conventional epoxy anti-corrosion coatings, these material barriers are still corroded quickly and the anti-corrosion coatings fall off quickly.
[0003] For these areas, a variety of primers + topcoats are usually used, such as setting a layer of epoxy zinc-rich primer for corrosion protection. However, since epoxy coatings are easily degraded and powdered under sunlight, one or more topcoats are usually required to block or absorb sunlight. Such a setting is not only costly, but also easily corroded by seawater, which leads to powdering of the epoxy zinc-rich primer, thereby shortening the life of the coating. Although there are some light stabilizers in the prior art, such as conventional 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole and hexamethylphosphoric triamide, adding them to epoxy coatings can reduce the impact of ultraviolet rays (mainly ultraviolet rays in sunlight that affect the coating) on the coating to a certain extent, but their effect is limited and has a certain impact on the corrosion resistance of the coating. Summary of the invention
[0004] To solve at least one of the above problems, the present invention provides an anti-ultraviolet coating composition resistant to seawater corrosion.
[0005] In order to achieve these purposes and other advantages of the present invention, a seawater corrosion-resistant anti-ultraviolet coating composition comprises, by weight, 50 to 80 parts of waterborne epoxy resin, 30 to 50 parts of filler, 10 to 40 parts of epoxy resin amino curing agent, 0.2 to 0.8 parts of dispersant, 0.5 to 2 parts of thickener, and 2 to 8 parts of nano aluminum powder;
[0006] The filler is a mixture of at least one of titanium dioxide, nano-silicon dioxide, talcum powder, and titanium iron powder and modified basalt flakes, and the size of the modified basalt flakes is not greater than 100 microns. The modified basalt flakes are prepared by the following method: 10 parts of basalt fibers are uniformly dispersed in water, followed by adding 0.5 to 2 parts of phytic acid and 0.5 to 2 parts of dopamine hydrochloride, followed by ultrasonic treatment for 40 to 60 minutes, and the pH of the dispersion is adjusted to be greater than 8 during the ultrasonic process.
[0007] For waterborne epoxy resin, common epoxy resins in the art can be purchased, such as the common E51 waterborne epoxy resin, which is a conventional commercial product in the art. For epoxy resin amino curing agent, common amino curing agents can be selected, such as fatty diamines, polyethylene polyamines, modified amino curing agents (such as 593 curing agent, etc.), and the addition amount of different curing agents is different, and the specific addition amount can be based on the existing curing agent, such as the addition percentage of 593 curing agent in E51 epoxy resin emulsion is usually 25-30%. In the present invention, the amino curing agent is used because the amino curing agent can make the epoxy resin cure at room temperature. Compared with the anhydride curing agent, the curing temperature of the amino curing agent is lower, and it can be cured under room temperature conditions.
[0008] In the present invention, among the fillers used, talcum powder, titanium dioxide, and nano-silicon dioxide are common pigments and fillers in coatings. At the same time, they all have a certain reflection effect on ultraviolet rays, which can reduce the influence of ultraviolet rays on the coating, but their influence on ultraviolet rays is relatively low. Although most coatings currently have one or more of talcum powder, titanium dioxide, and nano-silicon dioxide added, their ability to resist ultraviolet rays is relatively weak. Ferrotitanium powder is a composite metal material, which not only has strong wear resistance and corrosion resistance, but also has a certain antioxidant ability, which can reduce the influence of oxygen and the like on the coating.
[0009] As for basalt flakes, they have strong UV resistance, wear resistance and corrosion resistance. However, if basalt flakes are directly placed in the paint, due to the characteristics of the basalt flakes themselves, their compatibility with the paint is poor, and the coating is prone to cracking, resulting in coating failure. Phytic acid is a commonly used treatment agent for metal surfaces. It can passivate the metal surface, thereby improving the metal's corrosion resistance; at the same time, phytic acid also has antioxidant ability. Dopamine is a biomodified material that is easy to self-polymerize under alkaline conditions. The polymerized polydopamine has good adhesion properties. However, dopamine can usually only be polymerized under alkaline conditions.
[0010] For the above-mentioned materials, the inventors found after a large number of experiments that after treating the basalt flakes with phytic acid and dopamine, the compatibility of the basalt flakes and the coating can be significantly improved. At the same time, it can further enhance the corrosion resistance and UV resistance of the coating.
[0011] In the present invention, the reason why the pH of the solution is adjusted to above 8 during the ultrasonic process is mainly because dopamine will not polymerize under acidic conditions, and since phytic acid is acidic, the existing dopamine hydrochloride (most of the dopamine currently is dopamine hydrochloride) is also acidic, so it is necessary to drip alkali solution to make it alkaline to facilitate the polymerization of dopamine hydrochloride. At the same time, the inventors found that compared with directly adjusting the solution in the basalt flake modification process to alkaline, the method of gradually dripping alkali solution during the ultrasonic process is much more effective. Furthermore, the dripping time of the alkali solution is controlled to 10~30min, and the final coating effect is better.
[0012] In the present invention, the reason why nano aluminum powder is added is that the inventors have found that the added nano aluminum powder can greatly improve the UV resistance of the coating, and at the same time, the nano aluminum powder can also improve the corrosion resistance of the coating.
[0013] An embodiment of the present invention is that the thickener is one of carboxymethyl cellulose and polyurethane thickener.
[0014] One embodiment of the present invention is that the dispersant is a sodium polyacrylate dispersant.
[0015] One embodiment of the present invention is that the mass percentage of the modified basalt flakes in the filler is 10-30%. Theoretically, more modified basalt flakes can be added, but the price of basalt flakes is high, and even if more modified basalt flakes are added, the final performance changes little. Therefore, from an economic point of view, it is more reasonable to control the addition amount of modified basalt flakes to 10-30%.
[0016] In one embodiment of the present invention, the filler is a mixture of nano-silicon dioxide, talc, ferro-titanium powder and modified basalt flakes in a mass ratio of 30:15-20:8-12:10-15. Under this ratio, the obtained coating has a better effect.
[0017] One embodiment of the present invention is that the process of acid-treating basalt flakes is as follows: prepare an inorganic strong acid solution with a concentration of 1 to 3 mol / L, then add basalt flakes and make the inorganic strong acid solution cover the basalt flakes, react for 30 to 180 minutes under continuous stirring, take out the basalt flakes, then rinse with water until neutral and dry. Due to the characteristics of basalt flakes themselves, it is difficult for them to carry more phytic acid and dopamine. Therefore, the inventor increases the specific surface area of basalt flakes by acid-treating basalt flakes, so that the effect of modified basalt flakes is better; at the same time, the surface of the basalt flakes after acid treatment has certain hydroxyl and carboxyl groups, so that it can better carry phytic acid and dopamine.
[0018] Further, the inorganic strong acid is one of sulfuric acid or hydrochloric acid. Although nitric acid can also be used, the prices of hydrochloric acid and sulfuric acid are relatively low, while the price of nitric acid is relatively high. Considering the cost, it is better to use sulfuric acid or hydrochloric acid.
[0019] The present invention is beneficial in that:
[0020] The coating composition of the present invention not only has strong corrosion resistance, but also has good UV resistance, which can effectively enhance the UV resistance of the coating, so that the coating composition of the present invention can be better applied to outdoor open-air places, expand its application area, and extend the life of the coating. DETAILED DESCRIPTION
[0021] The present invention is further described below in conjunction with embodiments. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0022] In the following examples, unless otherwise specified, all operations used are routine operations in the art.
[0023] In the following examples, unless otherwise specified, all materials used are conventional materials in the art and mature commercial products.
[0024] In the following examples, the water-based epoxy resin used is E51 water-based epoxy resin.
[0025] In the following examples, unless otherwise specified, the parts are by mass.
[0026] Example 1: In this example, the coating composition includes the following components: 65 parts of epoxy resin emulsion, 38 parts of filler, 18 parts of epoxy resin 593 curing agent, 0.5 parts of sodium polyacrylate dispersant, 0.8 parts of carboxymethyl cellulose, and 6 parts of nano aluminum powder; wherein the filler is composed of nano silicon dioxide, talc, ferrotitanium powder and modified basalt flakes in a mass ratio of 30:18:10:12;
[0027] Modified basalt flakes are prepared by the following method:
[0028] S1. Prepare 2 mol / L sulfuric acid solution, take 150 mesh basalt flakes and add them into the sulfuric acid solution until the sulfuric acid solution just covers the basalt flakes, then react for 60 minutes under continuous stirring, take out the acid-etched basalt flakes, rinse with water several times until the washing water is neutral, and then dry the acid-etched basalt flakes;
[0029] S2. Take 10 parts of acid-etched basalt flakes and evenly disperse them in water, then add 1.5 parts of phytic acid and 1 part of dopamine hydrochloride, ultrasonicate for 50 minutes, take out the solid phase to obtain modified basalt flakes, and during the ultrasonication process, continuously add an aqueous solution of sodium hydroxide for 20 minutes, and maintain the pH of the dispersion at 8.5.
[0030] Example 2: In this example, the coating composition includes the following components: 57 parts of epoxy resin emulsion, 32 parts of filler, 5 parts of epoxy resin curing agent diethylenetriamine, 0.6 parts of sodium polyacrylate dispersant, 1 part of polyurethane thickener, 4 parts of nano aluminum powder; wherein the filler is composed of nano silicon dioxide, ferrotitanium powder and modified basalt flakes in a mass ratio of 30:22:15;
[0031] Modified basalt flakes are prepared by the following method:
[0032] S1. Prepare 1 mol / L hydrochloric acid solution, take 150 mesh basalt flakes and add them into the hydrochloric acid solution until the hydrochloric acid solution covers the basalt flakes by 2 cm, then react for 150 minutes under continuous stirring, take out the acid-etched basalt flakes, rinse with water several times until the washing water is neutral, and then dry the acid-etched basalt flakes;
[0033] S2. Take 10 parts of acid-etched basalt flakes and disperse them evenly in water, then add 1 part of phytic acid and 2 parts of dopamine hydrochloride, ultrasonicate for 50 minutes, take out the solid phase to obtain modified basalt flakes, and during the ultrasonication process, continuously add an aqueous solution of sodium hydroxide for 20 minutes, and maintain the pH of the dispersion at 8.5.
[0034] Example 3: The difference between this example and Example 1 is that the filler consists of titanium dioxide, talcum powder and modified basalt flakes in a mass ratio of 18:25:12, and the rest are the same.
[0035] Example 4: This example differs from Example 1 in that the preparation process of modified basalt flakes does not contain step S1, and the rest are the same.
[0036] Example 5: The difference between this example and Example 1 is that in step S2 of preparing the modified basalt flakes, sodium hydroxide solution is added before ultrasound to adjust the pH of the dispersion to 8.5, and the rest are the same.
[0037] Comparative Example 1
[0038] The difference between this comparative example and Example 1 is that the comparative example does not contain nano aluminum powder, and the rest is the same.
[0039] Comparative Example 2
[0040] The difference between this comparative example and Example 1 is that basalt flakes are used instead of modified basalt flakes, and the rest are the same.
[0041] Comparative Example 3
[0042] The difference between this comparative example and Example 1 is that phytic acid is not added during the preparation of the modified basalt flakes, and the rest are the same.
[0043] Comparative Example 4
[0044] The difference between this comparative example and Example 1 is that dopamine hydrochloride is not added during the preparation of the modified basalt flakes, and the rest are the same.
[0045] In order to further highlight the technical effects of the present invention, performance tests are performed on the above embodiments below.
[0046] 1. Salt spray resistance test: The compositions of Examples 1 to 5 and Comparative Examples 1 to 2 were sprayed on the parts to be protected by a compressed air sprayer to form a coating, which was then cured at room temperature for 5 days. The coating was then aged under 310 nm ultraviolet light for a period of time, and then subjected to a salt spray test according to the method specified in GB / T 1771-2007. The final results are shown in Table 1.
[0047] Table 1 Salt spray resistance test results
[0048]
[0049] It can be seen from Table 1 that the coating composition prepared in this embodiment has strong salt spray resistance and UV resistance; referring to Example 1 and Comparative Example 1, it can be seen that nano aluminum powder can effectively improve the UV resistance of the coating composition; referring to Example 1 and Comparative Example 2, it can be seen that the modified basalt flakes can effectively improve the salt spray resistance of the coating composition; referring to Example 1, Comparative Example 3 and Comparative Example 4, it can be seen that after adding phytic acid and dopamine to the modified basalt flakes at the same time, the effect of the coating composition can be effectively improved.
[0050] 2. Adhesion test
[0051] The compositions of Examples 1 to 5 and Comparative Examples 1 to 2 were sprayed on the parts to be anti-corrosion by a compressed air sprayer to form a coating, and then cured at room temperature for 5 days. They were then immersed in simulated seawater (sodium chloride content of 3.5 wt%) for 100 hours, and the adhesion test was carried out according to the method in GB / T 9286-2021. The final results are shown in Table 2.
[0052] Table 2 Adhesion test results
[0053]
[0054] It can be seen from Table 1 that the coating composition of the embodiment of the present invention has strong seawater corrosion resistance.
[0055] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A seawater corrosion-resistant UV-resistant coating composition, characterized in that: In parts by mass, it comprises 50-80 parts of waterborne epoxy resin, 30-50 parts of filler, 10-40 parts of epoxy resin amino curing agent, 0.2-0.8 parts of dispersant, 0.5-2 parts of thickener, and 2-8 parts of nano aluminum powder; The filler is a mixture of at least one of titanium dioxide, nano-silicon dioxide, talcum powder, and ferrotitanium powder and modified basalt flakes, and the size of the modified basalt flakes is not greater than 100 microns. The modified basalt flakes are modified by the following method: 10 parts of basalt flakes are uniformly dispersed in water, followed by adding 0.5 to 2 parts of phytic acid and 0.5 to 2 parts of dopamine hydrochloride, followed by ultrasonic treatment for 40 to 60 minutes, and the pH of the dispersion is adjusted to be greater than 8 during ultrasonic treatment.
2. The coating composition according to claim 1, characterized in that The thickener is one of carboxymethyl cellulose and polyurethane thickener.
3. The coating composition according to claim 1, characterized in that The dispersant is a sodium polyacrylate dispersant.
4. The coating composition according to claim 1, characterized in that The mass percentage of the modified basalt flakes in the filler is 10-30%.
5. The coating composition according to claim 1 or 4, characterized in that The filler is a mixture of nano silicon dioxide, talcum powder, ferrotitanium powder and modified basalt flakes in a mass ratio of 30:15-20:8-12:10-15.
6. The coating composition according to claim 1, characterized in that Before modifying the basalt flakes, the basalt flakes are acid-treated with an inorganic acid.
7. The coating composition according to claim 6, characterized in that The process of acid treatment of basalt flakes is as follows: prepare an inorganic strong acid solution with a concentration of 1~3mol / L, then add basalt flakes and make the inorganic strong acid solution cover the basalt scales, react for 30~180min under continuous stirring, take out the basalt scales, then rinse with water until neutral and dry.
8. The coating composition according to claim 6 or 7, characterized in that The inorganic strong acid is one of sulfuric acid or hydrochloric acid.
9. The coating composition according to claim 1, characterized in that The pH of the solution is adjusted to greater than 8 by adding alkali solution dropwise, and the alkali solution is added dropwise for 10 to 30 minutes.
Citation Information
Patent Citations
Seawater corrosion resistant coating composition and application thereof
CN118240455A
Basalt fiber reinforced polypropylene pipeline and preparation method thereof
CN118493955A